Pathogenetic mechanisms, epidemiology and classification of acute kidney injury in heart transplant recipients - I. L. Poz; A. G. Strokov; V. N. Poptsov; A. O. Shevchenko; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2021)
Kidney injury in heart transplant recipients is of a complex nature and bears the features of all types of cardiorenal interaction impairment. Pre-transplant renal dysfunction, perioperative acute kidney injury, as well as factors associated with graft and immunosuppression, determine the prevalence and severity of kidney pathology in this group of patients. This review examines the pathophysiology of kidney dysfunction in heart failure, the epidemiology, and criteria for acute kidney injury.